HUBUNGAN PENGETAHUAN, TINDAKAN MAKAN IBU HAMIL DAN STATUS GIZI IBU - Herdiani, Novera; Afridah, Wiwik (Jurnal Nutrire Diaita (Ilmu Gizi), 2017)
Nutritional problems is one of major public health problem which indirectly may elevate the risk for maternal and child mortality. The problem is preventable, and one of the risk factors is maternal eating behavior. The role of health professionals to provide nutritional counseling and monitor the pregnant women’s nutritional status is necessary for pregnant women in order that they want to behave and act to follow norms of nutrition and prevent complications as early as possible. The purpose of this study was to determine the relationship between the eating behavior of pregnant women and maternal nutritional status. The study design was cross-sectional, the sample was 42 pregnant women which selected by simple random sampling. The independent variable is the eating behavior which comprised from knowledge, and action while dependent variable is the maternal nutritional status based on body mass index. Chi square was performed to test the association with significance level of p  0.05. The results showed significant relationship between nutrition knowledge (p = 0.014), nutrition actions (p = 0.014) and maternal nutritional status, respectively. It is important to promote nutrition education among pregnant women to improve their nutritional status which in long term prevent maternal and infant mortality. Keywords: maternal behavior, nutrition education, nutritional status